PENYIDIKAN TINDAK PIDANA PEREDARAN PRODUK PANGAN ILEGAL OLEH BALAI BESAR PENGAWAS OBAT DAN MAKANAN BERDASARKAN UNDANG – UNDANG NOMOR 18 TAHUN 2012 TENTANG PANGAN DI PROVINSI RIAU - M Ichsyan; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Progress in the field of industry, which grew rapidly resulting in the emergence of the era of free market competition among manufacturers make increasingly stringent. Various methods are used by businesses to profit as much as possible, one of which is to distribute food products illegal.The purpose of this thesis, namely; First; To determine the Crime Investigation Illegal Circulation of Food Products by the Center for Food and Drug Administration in Riau Province Undan Under Law No. 18 Year 2012 on Food. Second: To determine the obstacles faced by the Center for Food and Drug Administration in a criminal investigation Illegal circulation of food products in the province of Riau, Third; To know the efforts made to overcome the obstacles faced by the Center for Food and Drug Administration in a criminal investigation Illegal circulation of food products in the province of Riau.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on a study in order to provide a complete and clear picture of the issues examined. This research was conducted at the Center for Food and Drug Administration, while the sample population is overall the parties relating to the issues examined in this study, the data source used, primary data, secondary document and document tertiary data collection techniques in this study with interviews and literature study.From the research there are three main issues that can be inferred. First, an investigation into the criminal distribution of food products ilegaln by the Center for Food and Drug Administration in Riau Province. Second, barriers are found in the investigation of criminal acts of illegal circulation of food products by the Center for Food and Drug Administration in the province of Riau. Third, efforts undertaken Civil Servant Investigators hall of the Food and Drug Administration in the province of Riau in Conducting Investigation Crime Illegal Circulation of Food Products In Riau province. Advice writer, first, the Center for Food and Drug Administration In Riau province to further optimize the investigation of cases of illegal distribution of food products. Second, the Party institutions involved in the crime of illegal distribution of food products, the government, and the merchants and the people must sit together to make a deal and of understanding. Third, the existence of legal counseling.Keywords : Investigation - Marketing Authorization - Food – Illegal